2014
DOI: 10.11622/smedj.2014017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between elderly inpatient fallers with and without dementia

Abstract: INTRODUCTIONThis study aimed to examine the various factors associated with inpatient falls among patients with and without dementia in a hospital setting. METHODSThis was a retrospective one-year study using data collected from Singapore General Hospital's electronic reporting system for inpatient falls. RESUlTSIn the study period, 298 patients aged ≥ 65 years fell during their hospital stay. The majority of the patients (n = 248) did not have dementia. In our study, fallers with dementia were more likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
(22 reference statements)
1
10
0
2
Order By: Relevance
“…Dementia was significantly associated with the risk of falling in our study, a factor that is also discussed in some previous studies . However, in these studies, the authors suggested that the risk of falling is rather related to spatial and memory functions, or considered that the fall cases linked to dementia were more probably associated with visual impairment or urinary incontinence, as well as with the use of walking aids (eg, walking stick).…”
Section: Discussionsupporting
confidence: 64%
“…Dementia was significantly associated with the risk of falling in our study, a factor that is also discussed in some previous studies . However, in these studies, the authors suggested that the risk of falling is rather related to spatial and memory functions, or considered that the fall cases linked to dementia were more probably associated with visual impairment or urinary incontinence, as well as with the use of walking aids (eg, walking stick).…”
Section: Discussionsupporting
confidence: 64%
“…Throughout the literature, nurses consistently report that ‘containment’ through the use of disposable continence pads and catheters as a key strategy for the management of continence for hospitalised older adults [ 25 ]. These approaches have implications for the occurrence of avoidable harm and patient outcomes during an acute admission; incontinence is a common risk factor for falls [ 26 , 27 ], and catheters are associated with high rates of urinary tract infections [ 28 ]. These factors are also associated with a greater financial burden, prolonged hospitalisation, re-admission, and increased mortality [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Falls may result in injuries, such as fractures or subdural hematomas, leading to longer hospital stays 1 and higher medical costs 2,3 . Psychiatric patients are at a higher risk of falls owing to psychological disorders, 4 such as depression 5‐7 and cognitive impairment 8‐10 . These patients tend to incur injuries or functional decline 11,12 and worsening mental symptoms 13,14 after falls.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Psychiatric patients are at a higher risk of falls owing to psychological disorders, 4 such as depression [5][6][7] and cognitive impairment. [8][9][10] These patients tend to incur injuries or functional decline 11,12 and worsening mental symptoms 13,14 after falls. Psychotropic drugs are known to increase the risk of falls.…”
Section: Introductionmentioning
confidence: 99%